Analisis Kemampuan Penalaran Matematis Peserta Didik SMP Ditinjau dari Kemandirian Belajar - Saffanah Ziyan Salsabiela; Fatimatul Khikmiyah; Syaiful Huda (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze junior high school students’ mathematical reasoning abilities in terms of their levels of learning independence. The research employed a descriptive qualitative approach involving three ninth-grade students from UPT SMP Negeri 5 Gresik, each representing high, medium, and low levels of learning independence. Data were collected through a self-regulated learning questionnaire, a mathematical reasoning test based on the topic of Systems of Linear Equations in Two Variables (SPLDV), and semi-structured interviews. Data analysis followed Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The results revealed that students with high learning independence demonstrated strong reasoning skills across all seven indicators of mathematical reasoning (representing statements, making conjectures, performing manipulations, constructing proofs, drawing conclusions, verifying arguments, and identifying patterns). Students with medium learning independence fulfilled only some indicators, while those with low learning independence could only make simple conjectures without systematic reasoning. These findings highlight that learning independence plays a crucial role in developing mathematical reasoning, as it enables students to regulate their thinking processes, evaluate solutions, and correct errors. Teachers are encouraged to integrate learning strategies that foster self-regulation—such as the CORE and Flipped Classroom models—to enhance students’ mathematical reasoning skills.